Pengaruh Manajemen Supervisi Kepala Sekolah Terhadap Kinerja Pegawai di Sekolah Menengah Kejuruan Negeri (SMKN) - Rosantia, Rosantia; Durtam, Durtam; Santoso, Sigit (IAIN Syekh Nurjati Cirebon, 2024)
The results of observations made by researchers at the State Vocational High School 1 Gantar Indramayu, found several problems, the lack of professionalism of some employees in carrying out there main duties and functions and the less than optimal supervisory role of the school principal. Some of these problems can hinder the learning and teaching process at school. This study aims to determine the effect of principal supervision on employee performance at the State Vocational High School 1 Gantar Indramayu, this study uses a descriptive quantitative approach. This study used the Slovin formula proportionate simple random sampling technique where the sample of this study amounted to 50 employees out of 102 total employees. The main data collection technique is using a questionnaire distributed to 50 employees. Observation techniques and documentation studies were carried out to support the results of this study. Based on data analysis using SPSS version 22, the t statistical test found t count 3.365> 1.677 t table or Sig. 0.002 <0.05 then Ho is rejected and Ha is accepted. This means that the principal's supervision has a effect on employee performance at the State Vocational High School 1 Gantar Indramayu. In the calculation of the coefficient of determination, it is known that the effect of principal supervision on employee performance at the State Vocational High School 1 Gantar Indramayu is 19.1% while the remaining 81% is influenced by other variables not examined in this study. From the results of these calculations, there is a influence between the principal's supervision on employee performance at the State Vocational High School 1 Gantar Indramayu.